Decoding identity shifts in Chinese EFL pre-service teachers: insights from the intersubjectivity FLT model - Jiahua Ye; Wenbo Fan; Yongxiang Wang (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract Teacher identity exploration in English language teacher education has taken on a heightened level of significance. Despite extensive research on pre-service English teachers’ initial pedagogical experiences, there remains a notable gap in understanding their transformations during and after teaching practice. To bridge this research gap, this study utilizes a semi-structured interview with 30 Chinese pre-service teachers to obtain deep insights into the shifts in Chinese EFL pre-service teachers’ professional identities before and after their practicum, with a pointed focus on the effects of the intersubjectivity foreign language teaching model (the intersubjectivity FLT model). This model, as investigated in this study, emphasizes collaborative participation, equitable dialogue, multiple integration, and a dynamic classroom environment. With MAXQDA software (v. 2024), thematic analysis revealed critical insights into Chinese EFL pre-service teachers’ identity shifts, driven by the intersubjectivity FLT model. This study finds that teachers transitioned from static authority to adaptable, engaged participants, facilitated by the integration of multiple dialogue and the model’s unifying role in connecting practicum, student feedback, and reflection for cohesive identity development. This study presents implications for refining the theoretical framework within the domain of English teacher education, providing invaluable insights for the professional development of pre-service teachers.